What Does Temporal Brain Signal Complexity Reveal About Verbal Creativity? - Kaur, Yadwinder; Ouyang, Guang; Sommer, Werner; Weiss, Selina; Zhou, Changsong; Hildebrandt, Andrea (Frontiers in Behavioral Neuroscience, 2020)
Recent empirical evidence reveals that creative idea generation builds upon an interplay of multiple neural networks. Measures of temporal complexity yield important information about the underlying mechanisms of these co-activated neural networks. A few neurophysiological studies investigated brain signal complexity during the production of creative verbal associations and resting states, aiming to relate it with creative task performance. However, it is unknown whether the complexity of brain signals can distinguish between productions of typical versus original verbal associations. In the present study, we investigated verbal creativity with Multi-Scale Entropy (MSE) of EEG signals, which quantifies complexity over multiple time scales, capturing unique dynamic features of neural networks. MSE was measured in verbal Divergent Thinking (DT) states while emphasizing on producing either typical verbal associations or original verbal associations. We hypothesized that MSE differentiates between brain states characterizing the production of typical versus original associations and is a sensitive neural marker of individual differences in producing original associations. Results from a sample of N = 92 young adults revealed slightly higher average MSE for original as compared with typical association production in small and medium time scales at frontal electrodes and slightly higher average MSE for typical association production in higher time scales at parietal electrodes. However, measurement models failed to uncover specificity of individual differences as MSE in typical versus original associations was perfectly correlated. Hence, individuals with higher MSE in original associations condition also exhibit higher MSE during the production of typical associations. The difference between typical and original associations MSE was not significantly associated with human-rated originality of the verbal associations. In sum, we conclude that MSE is a potential marker of creative verbal association states, but replications and extensions are needed, especially with respect to the brain-behavior relationships.